bcl Morphology Formation Strategy on Nanostructured Titania via Alkaline Hydrothermal Treatment - Fry Voni Steky; Didi Prasetyo Benu; Muhammad Reza; Damar Rastri Adhika; Viny Veronika Tanuwijaya; Ashari Budi Nugraha; Veinardi Suendo; Rino Rakhmata Mukti (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
Titanium dioxide (TiO2) is a semiconductor material that plays an important role in photocatalysis. Bicontinuous concentric lamellar (bcl) is an interesting morphology with an open channel pore structure that has been successfully synthesized on silica-based materials. If bcl morphology can be applied in TiO2 system, then many surface properties of TiO2 can be enhanced, i.e. photocatalytic activity. A simple and effective strategy has been demonstrated to transform aggregated and spherical TiO2 particles to bcl morphology via alkaline hydrothermal route. Alkaline hydrothermal treatment successfully transforms TiO2 particle surface to have bcl morphology through swelling with ammonia then followed by phase segregation process. We proposed this strategy as a general pathway to transform the particle surface with any shape to have bcl morphology.